2006
DOI: 10.3201/eid1708.060264
|View full text |Cite
|
Sign up to set email alerts
|

Qinghai-like H5N1 from Domestic Cats, Northern Iraq

Abstract: All patients with seropositive samples lived in the urban centers. The mean age of the 6 patients was 36.0 years (range 24-56 years), and 83% were men. Test results for IgM antibodies to SNV conducted on samples in parallel were negative.The seroprevalence found in this study was caused by patient exposure to hantavirus. However, in the absence of IgM to SNV, we cannot link the respiratory symptoms observed to recent infection with hantavirus. Lack of information about the patients, especially their clinical h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 9 publications
(9 reference statements)
1
59
0
1
Order By: Relevance
“…Meanwhile, natural infection of felids has been reported from seven countries in Asia, the Middle East and Europe including China (http://www.promedmail.org; archive number 20041023.2873), Thailand (Keawcharoen et al, 2004;Thanawongnuwech et al, 2005;Songserm et al, 2006), Vietnam (http://www.promedmail.org; archive number 20050826.2527), Indonesia (http://www.promedmail. org; archive number 20070126.0347), Iraq (Yingst et al, 2006), Austria (Leschnik et al, 2007) and Germany (Klopfleisch et al, 2007;Weber et al, 2007 , attachment to type II pneumocytes and virus replication in type I and type II pneumocytes . Diseased cats excreted virus via the respiratory tract and, at relatively low titres, also via the digestive tract Rimmelzwaan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, natural infection of felids has been reported from seven countries in Asia, the Middle East and Europe including China (http://www.promedmail.org; archive number 20041023.2873), Thailand (Keawcharoen et al, 2004;Thanawongnuwech et al, 2005;Songserm et al, 2006), Vietnam (http://www.promedmail.org; archive number 20050826.2527), Indonesia (http://www.promedmail. org; archive number 20070126.0347), Iraq (Yingst et al, 2006), Austria (Leschnik et al, 2007) and Germany (Klopfleisch et al, 2007;Weber et al, 2007 , attachment to type II pneumocytes and virus replication in type I and type II pneumocytes . Diseased cats excreted virus via the respiratory tract and, at relatively low titres, also via the digestive tract Rimmelzwaan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The virus is propagated in the lower respiratory tract after infection of type II pneumocytes that line the alveoli ; replication in the lung leads to foci of alveolar damage. The virus eventually reaches the liver, heart, brain, renal glomeruli, adrenal gland and sometimes the spleen and pancreas Songserm et al, 2006a); it has also been found in the large intestine (Yingst et al, 2006). Infection of internal organs suggests systemic spread through viraemia, but so far no virus has been isolated from blood .…”
Section: Pathogenesismentioning
confidence: 99%
“…Both routes can be suspected upon cat-to-cat virus transmission. Virus has repeatedly been isolated from saliva, the trachea and intestinal contents as well as from urine and faeces of infected cats Songserm et al, 2006a;Yingst et al, 2006). It is therefore assumed that first replication takes place in the upper respiratory and digestive tracts.…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The detection involved virus isolation, serosurveillance and genomic studies (Crawford et al, 2005;Kuiken et al, 2006;Songserm et al, 2006b;Yingst et al, 2006;Klopfleisch et al, 2007;Daly et al, 2008;Song et al, 2008;Sponseller et al, 2010;Song et al, 2011;Zhan et al, 2012). In Nigeria, serosurveillance had shown the presence of CIV in dogs.…”
Section: Epidemiologymentioning
confidence: 99%